Arsitektur Enterprise Data Management Untuk Unit Kegiatan Mahasiswa & Organisasi Mahasiswa di STMIK Komputama Majenang - Mahardika, Fajar; Bambang Sumantri, R Bagus (Jurnal Teknologi dan Bisnis, 2020)
The development of Private Universities from year to year is growing. This is directly proportional to the development of student organizations and student activity units. One of the private universities is STMIK Komputama Majenang. STMIK Komputama consists of several Student Activity Units and Student Organizations. STMIK Komputama also has 3 campuses in which each campus has several Student Activity Units and the same Student Organization. With the existence of these 3 campus units, STMIK Komputama Majenang has difficulty in terms of coordination and also the synchronization of the Activities Agenda of the Student Activity Units and Student Organizations. The Enterprise Data Management Architecture is used to connect 3 campuses belonging to STMIK Komputama Majenang. Enterprise Data Management Architecture is the application of architecture used to carry out data management in a Student Activity Unit and Student Organization. In this research, an architecture that is able to synchronize and also produce a good planning of activities in 3 campus of STMIK Komputama Majenang